Five new Penaincisalia species (Lepidoptera: Lycaenidae: Eumaeini) from the Andes of southern Ecuador and northern Peru - Hall, Jason P.w.; Willmott, Keith R.; Busby, Robert C. (Zootaxa, 2005)
Five new species of Penaincisalia (Lycaenidae: Eumaeini) are described from the high Andes of southern Ecuador and northern Peru: P. caeruleanota Hall & Willmott n. sp., P. juliae Hall & Willmott n. sp., P. andreae Busby & Hall n. sp., P. libertada Hall n. sp. and P. ismaeli Busby & Hall n. sp.. We present brief discussions on their systematic placement within the genus and on their adult ecology.